Застосування двобічних ітераційних методів у математичному моделюванні термохімічних процесів (одновимірний випадок) - Янбеков, Р. Я. (ХНУРЕ, 2023)
The paper considers the application of bilateral iterative methods to the solution of the first boundary value problem for an ordinary semi-linear differential equation with the Helmholtz operator, which occurs in mathematical modeling of thermochemical processes.
Keywords: стаціонарні термохімічні процеси; двобічні ітераційні методи; інтегральне рівняння Гаммерштейна; функція Гріна